GAMBARAN KEJADIAN EFEK SAMPING PADA PENGGUNAAN OBAT OFF LABEL PASIEN LUPUS - Iwan Yuwindry; Noval (Sekolah Tinggi Ilmu Kesehatan Borneo Lestari Banjarbaru, 2020)
Systemic lupus erythematosus is a chronic autoimmune inflammatory disease whose cause is not yet clear, has a wide variety of clinical features and diverse appearance of the disease course. The use of off label drugs such as corticosteroids for the treatment of SLE can result in a large potential side effect for Lupus patients. This study aims to determine the description of the occurrence of side effects on the use of drugs off lupus patients.This research was conducted using a descriptive observational research designby surveying using the Naranjo Algorithm instrument with 28 respondents. Based on research conducted, it was found that the side effects of using off label drugs showed that 12 respondents or 43% experienced Probable classification (most likely ROM. IO). These results indicate that the use of off-label drugs in lupus therapy can pose a risk of the possibility of adverse drug reactions.